2014
DOI: 10.1074/jbc.m113.525683
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Rv2179c Protein Establishes a New Exoribonuclease Family with Broad Phylogenetic Distribution

Abstract: Background: More than 25% of Mtb proteins have unknown functions, limiting our understanding of Mtb physiology and pathogenesis. Results: The hypothetical Mtb protein Rv2179c is a new DEDD-type exoribonuclease. Conclusion: Rv2179c is the founding member of a new exoribonuclease family with broad phylogenetic distribution. Significance: Assigning RNase function to Rv2179c provides annotation for hundreds of bacterial orthologs and provides a new view of RNA processing in Mtb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Recent work has demonstrated that Rho terminated transcripts have processed 3′ ends immediately downstream of a stable stem‐loop (Dar & Sorek, ). While few RNA processing enzymes of mycobacteria have been well characterized, the Mtb genome encodes many known RNases with varying sequence specificities (Abendroth et al, ; Taverniti, Forti, Ghisotti, & Putzer, ; Uson, Ordonez, & Shuman, ; Zeller et al, ; Zhu et al, , ). We speculate that unidentified TB‐complex RNA chaperones and/or modifying enzymes contribute to Mcr11 stability, and that their absence in Msm results in Mcr11 degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has demonstrated that Rho terminated transcripts have processed 3′ ends immediately downstream of a stable stem‐loop (Dar & Sorek, ). While few RNA processing enzymes of mycobacteria have been well characterized, the Mtb genome encodes many known RNases with varying sequence specificities (Abendroth et al, ; Taverniti, Forti, Ghisotti, & Putzer, ; Uson, Ordonez, & Shuman, ; Zeller et al, ; Zhu et al, , ). We speculate that unidentified TB‐complex RNA chaperones and/or modifying enzymes contribute to Mcr11 stability, and that their absence in Msm results in Mcr11 degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The processing of these discrete ends is dependent on the redundant action of the 3’ → 5’ exonucleases PNPase and RNase II, and it was speculated that the stem-loop promotes stabilization of the processed transcript (71). While few RNA processing enzymes of mycobacteria have been well characterized, the Mtb genome encodes many known RNases with varying sequence specificities (72-77). We speculate that unidentified TB-complex RNA chaperones and/or modifying enzymes contribute to Mcr11 stability, and that their absence in Msm results in Mcr11 degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than targeting low-homology (unannotated) proteins to fill-out 'fold-space', the TBSGC has instead applied the concept of a highthroughput pipeline to determining the structures of functionally important proteins [107,108], to improve our understanding of metabolic pathways, and ultimately to facilitate the drug discovery process. [109][110][111], to assign functions to previously uncharacterized or "hypothetical" proteins [112][113][114],…”
Section: Accepted Manuscriptmentioning
confidence: 99%